Staffing at Ambulatory Endoscopy Centers in the United States: Practice, Trends, and Rationale - Deepak Agrawal; Rajeev Jain (Gastroenterology Research and Practice)
Background. Endoscopy nurse (RN) has a pivotal role in administration and monitoring of moderate sedation during endoscopic procedures. When sedation for the procedure is administered and monitored by an anesthesia specialist, the role of an RN is less clear. The guidelines on this issue by nursing and gastroenterology societies are contradictory. Methods. Survey study of endoscopy lab managers and directors at outpatient endoscopy units in Texas. The questions related to staffing patterns for outpatient endoscopies and responsibilities of different personnel assisting with endoscopies. Results. Responses were received from 65 endoscopy units (response rate 38%). 63/65 (97%) performed at least a few cases with an anesthesia specialist. Of these, 49/63 (78%) involved only an endoscopy technician, without an additional RN in the room. At 12/49 (25%) units, the RN performed tasks of an endoscopy technician. At 14/63 (22%), an additional RN was present during endoscopic procedures and performed tasks not directly related to patient care. Conclusions. Many ambulatory endoscopy units do not have an RN present at all times when sedation is administered by an anesthesia specialist. An RN, when present, did not perform tasks commensurate with the education and training. This has implications about optimal utilization of nurses and cost of performing endoscopies.